Mobility, space and urbanism: a study of practices and relationships among migrants from African countries in Cape Town, South Africa - Chekero, Tamuka (Social Anthropology, 2023)
This study examines the ways in which migrants' diverse experiences in urban Cape Town are mediated by their mobility, movement, and circulation of necessary livelihood objects and ideas. I explore how social formations are individually and collectively created and co-created by migrants' daily interactions, encounters, experiences, and social dynamics in the city. The research is innovative in its deliberate option not to classify migrants based on their country of origin (except where necessary to explain the experiences of actors), thereby challenging stereotypes and preconceptions about African migrants and migration as “people out of place”. Data for this study were gathered using a multi-sited ethnography between 2019 and 2021. Numerous visits in various Cape Town neighbourhoods, observations, interactions, and participation in migrants' social activities, as well as formal and informal interviews and group discussions with a sample of Cape Town's migrant population, were used. The data gathered were analysed using the framework of incompleteness and conviviality, to understand how migrants in Cape Town foster and sustain social networks, such as hushamwari (friendship) and mutuality inspired by ubuntu. The empirical data reveals that the category “migrant” generates and reinforces particular kinds of “borders” and “boundaries” that limit and restrict the mobility potential, access to space and livelihood opportunities of the people so categorized. Some of these obstacles consist of profiling based on belonging and non-belonging, roadblocks set up by law enforcement and local hostilities that implicitly or overtly target them. Due to the precarious nature of their situation, migrant women are confronted with a greater number of challenges. In addition to these challenges, the onset of the COVID-19 pandemic added another layer of difficulty to the problems that migrants face. Their livelihoods, sources of income, and as a direct result, remittances were all negatively impacted. In coping with the challenges, migrants form connections with diverse people and embrace various social networks, such as hushamwari, inspired by ubuntu and conviviality. Social networks are an important factor in assisting migrants in gaining access to opportunities for livelihood, sending available money and goods home (during the COVID-19 lockdown) and developing sociality. Even though social networks exist, they are not easily accessible to everyone and will not last indefinitely. They may suffer and strain since they are not immune to conflicts, friction and tension. Conflicting religious practices, beliefs, and values have been demonstrated to strain and pose challenges to migrant social networks. Though social networks may be disputed among migrants as a result of conflict, the social bonds made through conviviality, mutuality, hushamwari and ubuntu appear to be strong and promising. By embracing these concepts, this study portrays migrants as rational individuals who rely on numerous interconnections and creative interdependencies to survive in Cape Town. In conclusion, this study underscores that more than nationality, networks such as hushamwari, which are built on incompleteness, ubuntu, and conviviality are more important in the everyday interactions, encounters, and livelihood struggles of migrants, and it is important to foreground this in research on urbanism and its cosmopolitan imperative.